2016
DOI: 10.5935/abc.20160099
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fetal Hypothyroidism on Cardiac Myosin Heavy Chain Expression in Male Rats

Abstract: Background:Thyroid hormone deficiency during fetal life could affect the cardiac function in later life. The mechanism underlying this action in fetal hypothyroidism (FH) in rats has not been elucidated thus far.Objective:The aim of this study is to evaluation the effect of FH on cardiac function in male rats and to determine the contribution of α-myosin heavy chain (MHC) and β-MHC isoforms.Methods:Six pregnant female rats were randomly divided into two groups: The hypothyroid group received water containing 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…Importantly, our previous studies have shown that 10-12-week-old offspring of dams treated with PTU using the same protocol as in this work had normal levels of total and free T4 and T3, as well as TSH for a least a month ( Gaynullina et al, 2017 , 2018b ). This is consistent with other studies of gestational hypothyroidism ( Gilbert and Sui, 2006 ; Taylor et al, 2008 ; Ghanbari et al, 2015 ; Yousefzadeh et al, 2016 ). Moreover, adult rats with antenatal/early postnatal hypothyroidism demonstrate normal blood levels of total cholesterol and triglycerides ( Gaynullina et al, 2017 ), thus they had no lipid metabolism disorders which might be an independent factor influencing vascular function.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Importantly, our previous studies have shown that 10-12-week-old offspring of dams treated with PTU using the same protocol as in this work had normal levels of total and free T4 and T3, as well as TSH for a least a month ( Gaynullina et al, 2017 , 2018b ). This is consistent with other studies of gestational hypothyroidism ( Gilbert and Sui, 2006 ; Taylor et al, 2008 ; Ghanbari et al, 2015 ; Yousefzadeh et al, 2016 ). Moreover, adult rats with antenatal/early postnatal hypothyroidism demonstrate normal blood levels of total cholesterol and triglycerides ( Gaynullina et al, 2017 ), thus they had no lipid metabolism disorders which might be an independent factor influencing vascular function.…”
Section: Discussionsupporting
confidence: 93%
“…Mechanistic studies of developmental hypothyroidism effects involve different animal models, among which the model of supplementation with antithyroid drug propylthiouracil (PTU) is often used ( Santos et al, 2012 ; Ghanbari et al, 2015 ; Yousefzadeh et al, 2016 ; Gaynullina et al, 2017 , 2018b , 2018a ). When female rats are treated by PTU during the whole gestation and 2 weeks postpartum, the offspring is hypothyroid at the age of 2 weeks ( Gaynullina et al, 2017 , 2018b ), but becomes euthyroid since at least 6 weeks of age ( Gaynullina et al, 2018a ).…”
Section: Introductionmentioning
confidence: 99%
“…Contracture disorders of myofibrils, at the time of their formation, can be clinically manifested by cardiac arrhythmias, and subsequently lead to the loss of the ability to contract this area of the cardiomyocyte, which can lead to both a decrease in heart rate and a decrease in cardiac output. At the same time, hypothyroidism is indeed clinically manifested by similar myocardial symptoms [27]. Thus, the histopathological changes we found in the structure of the contractile apparatus are characteristic clinical signs of this endocrine nosology [30,31].…”
Section: Resultssupporting
confidence: 62%
“…The visually recorded thinning of myofibrils in hypothyroidism may be due to a decrease in the formation of myosin protein in contractile cardiomyocytes, as reported in the molecular genetic study by N. Yousefzadeh et al, where the researchers reported a decrease in the expression of the myosin protein isoform characteristic of adults (heavy chain isoform alpha-myosin), in the myocardium of rats under conditions of hypothyroidism. A decrease in the expression of the adult myosin isoform was accompanied by a compensatory increase in the expression of the fetal myosin isoform (betamyosin heavy chain isoform) and weakening of the contractile function of the heart, in particular, a decrease in the frequency and strength of heart contractions [27,28]. Similar changes in the qualitative and quantitative composition of myosin protein isoforms and impaired contractile function were also noted in striated skeletal muscle tissue [29].…”
Section: Resultsmentioning
confidence: 78%
“…At the end of treatments, animals were fasted for 8 h and then were anesthetized through intraperitoneal co-administration of ketamine (60 mg/kg) and xylazine (10 mg/kg) (Yousefzadeh et al 2016). Th en, liver samples immediately removed for additional analysis.…”
Section: Methodsmentioning
confidence: 99%